Impact of Supply Chain Governance on Financial Reporting: Evidence from Iraq - Abdalameer Zamil Latif; Hassan N. Malkh; Assad AL-Khalidi (International Journal of Supply Chain Management, 2019)
The importance of supply chain governance mechanism has grabbed the attention of academia due to massive corporate scandals in 21st century. The following study is aimed to investigate the supply chain governance mechanism in Iraqi corporations at first stage and develop the relationship between supply chain governance with quality of financial reporting at second stage. The sample of this study is consists of listed Iraqi companies between the time period of 2009 to 2016. A panel regression technique is applied to investigate the proposed framework by fulfill the objective of this investigation. Results revealed that board independence has a significant and positive role on financial reporting quality. Whereas, board size and CEO duality have a negative association with financial reporting quality. Furthermore, firm size and age was considered as control variables which influence the relationship of supply chain governance and quality of financial reporting.